Ìgbélárugẹ Èdè: Akinwumi Isola’s Model for Promoting African Languages - Akinloye Ojo (Yoruba Studies Review, 2021)
The ever-popular discussion in African literary circles is critically about language choices that African writers make in their creative endeavors. This is part of this write-up’s focus plus the plight of African languages with attention to the benefit and challenges for their empowerment. We set out to achieve two goals in this essay; first contributing to the ongoing discussions on African mother tongues, their vital roles in African literatures while characterizing pointers on proficiency and performance. Second, considering the use of Yoruba language in creative works of late Akínwùmí Oròjídé Iṣọ̀lá. Expectedly, the latter goal will exemplify the importance of indigenous languages to African writers. In pursuance of these dual goals, it is critical to highlight areas in which African writers, especially those writing in their native African languages, have endured to play crucial roles in promotion of African languages. These highlighted areas go beyond now fashionable and expressed goal of focusing on literature in African languages (splendor in African languages) onto push for fairness for languages and their speakers (linguistic justice).